MENGUJI RELEVANSI TEORI JEAN PIAGET TERHADAP PERKEMBANGAN BERPIKIR OPERASIONAL KONKRET ANAK SEKOLAH DASAR DI ERA MODERN - Yosua Rahanubun; Juleha Pesilette; Hunahani Nahatue; Asrina Banjar; Jenny Koce Matitaputty (ITB AAS Indonesia Surakarta, 2026)
Abstract This article reexamines the relevance of Jean Piaget's cognitive development theory, particularly the concrete operational stage, to the thinking patterns of elementary school children in the modern era. Using a literature review method, this study compares Piaget's classical theory with recent research findings that describe the influence of technology, digital media, and socio-cultural contexts on children's cognitive development. The results of the study show that although the basic principles of Piaget's theory are still relevant, today's children exhibit new dynamics in logical thinking due to exposure to technology and digital learning environments. Modern children are able to understand symbols and abstract concepts more quickly, but sometimes experience difficulties in concentration and social interaction. Therefore, Piaget's theory needs to be interpreted contextually, taking into account cultural factors and technological developments, in order to remain effective as a basis for learning in elementary schools. Keywords: Piaget, concrete operational, cognitive, elementary school children, modern era